Smart City: Public Parking Dashboard - Klandev, Ivan; Tolevska, Marta; Trajanov, Dimitar (Ss. Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2020)
It is widely known that finding an available parking slot during peak hour is a significant issue in cities. Drivers are spending large amount of time in search of a free spot where they can properly park their car. The purpose of providing these visualizations is to have a visualized preview of the data collected from different parking events, in order to spot improper parked vehicles, find causes for jammed areas, find places where there is a need for building a parking garage and etc. Considering the popularity and evolution of Internet of Things and their usage in the development of smart cities, these visualizations are providing crucial information. That information will help distinct areas that have a need of implementing some system regarding smart city, from another areas that are not that crowded and there is no need of any changes. All these benefits will also lead to reduction of expenses, pollution and traffic jams, while the income will rise.
Keywords: smart city, public parking, visualization, dashboard